(untitled) (Research, Society and Development, 2020)
The objective of this study is to identify, from the memories of Physical Education academics, the sports practices they had access to in primary and secondary school. We selected 102 academics, between 18 and 35 years old, 52 females and 50 males. The data were obtained through a questionnaire and analyzed through a specific sports classification. We identified that most of the experiences were restricted to two types of sports: invasion sports and net sports; with the predominance of one sport within each group: Futsal and Volleyball. We found that, although the content of the sports is most used in Physical Education classes, the participants of the study did not study the diversity within the field of Sports in school.